Engineered E. coli Nissle 1917 for the delivery of matrix-tethered therapeutic domains to the gut - Pichet Praveschotinunt (Nature Portfolio, 2019)
Anti-inflammatory treatments for gastrointestinal diseases can often have detrimental side effects. Here the authors engineer E. coli Nissle 1917 to create a fibrous matrix that has a protective effect in DSS-induced colitis mice.